Analisa Agregat Halus Pasir Zona III Dengan Agregat Kasar Ukuran 20 mm Dan 40 mm Untuk Uji Kuat Tekan Mutu Beton Pada Campuran Beton Normal - Nasir Bumulo; Nur Windawaty Rusnadin (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Concrete is a construction material that is widely used in building structutre work in indonesia becouse it has many benefits. Its compactness and cooperation arragement is very influential toward the compressive strength. One factor is the compectness of concrete fine aggregate and coarse aggregate. The aim of this research was to find out compessive strength of concrete at 28 days using sand material zone III with pebbles the size of 20 mm and 40 mm in a normal concrete mix.The reseach was using the quantitaive testing method. The independent variable of this research was the composition of the mixture, and dependent variable was in the form of concrete quality. The control variable was the material being used. The data collection was done by conducting laboratory testing based on SNI and PBI. The data analysis was done by calculating the average of the test results are then compered with SNI and PBI.The result of concrete research with sand material of zone III and gravel of 20 mm and 40 mm was observed at 28 days old showed a compressive strength value of 311,89 Kg / cm2. Then the concrete sample with sand material of zone III and pebble size 40 mm shows the value of compressive strength of 334,46 Kg / cm2. From this result, it can be concluded that the mixture of sand zone III with gravel measuring 40 mm has a value of concrete compressive strength greater than 20 mm.